آليات الموازنة بين فكرة الأمن القانوني وأثر مبدأ رجعية إلغاء الأوامر الرئاسية قانون الانتخابات 01/21 أنموذجا’ - دراز سعيد; مولود منصور (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه المقالة البحثية الى إيجاد نوعا من التوازين بين مبدأين ضروريين لإقامة دولة القانون وهما، مبدأ رجعية أثر إلغاء الأوامر الرئاسية من طرف البرلمان ومبدأ الأمن القانوني، وتتجلى مشكلة هذا البحث في: ما هي الآليات القانونية الكفيلة لتحقيق الموازنة؟ انطلاقا من فرضية الغاء الأوامر الرئاسية من طرف البرلمان بأثر رجعي. وقد قسمنا الدراسة إلى مبحثين، خصصنا المبحث الأول لمفهوم المبدأين السابقين ومبررات تطبيقهما، في حين خصصنا المبحث الثاني لبيان آليات الموازنة بينهما وتطبيقاتهما في التشريع، وتوصلنا الى جملة من النتائج منها: أولها أن الأمن القانوني هو إشعار الأفراد أن حقوقهم ومراكزهم القانونية محل اهتمام سلطات الدولة، ثانيها هي أن إلغاء الأمر الرئاسي الخاص بقانون الانتخابات 21/01 لا يؤدي الى إلغاء المجلس الشعبي الوطني المنتخب في ظل هذا القانون. Abstract: This research article aims to find a kind of balance the two necessary principles of the rule of law, namely, the retroactive effect of the repeal of presidential orders by Parliament and the principle of legal security, the problem of which is reflected in: What are the legal mechanisms for achieving the balance? Based on the premise that presidential orders were rescinded by Parliament retroactively. We divided the study into two researchers. We devoted the first research to the concept of the two preceding principles and the rationale for their application. The second study was devoted to indicating the mechanisms for balancing them and their applications in legislation. We reached a number of results, including: First, legal security is to notify individuals that their legal rights and status are of interest to the State authorities. Second, the repeal of Presidential Order No. 21/01 does not lead to the abolition of the people’s national assembly under this law.